A Flow Control Scheme Based on Per Hop and Per Flow in Commodity Switches for Lossless Networks - Shie-Yuan Wang (IEEE, 2021)
Performing flow control inside a network can effectively avoid packet loss due to buffer overflow in switches. IEEE 802.3x exercises a per-hop link-based flow control scheme to achieve this goal. IEEE 802.1Qbb Priority-based Flow Control (PFC) improves IEEE 802.3x by proposing a per-hop per-service-class flow control scheme. Although PFC is better than IEEE 802.3x, it still suffers from several serious problems such as congestion spreading, deadlock, and packet loss. In this work, we propose a per-hop per-flow scheme to mitigate these problems. We design, implement, and evaluate the performance of our scheme in P4 hardware switches. Experimental results show that (1) our scheme outperforms PFC in many aspects including avoiding congestion spreading, deadlock, and packet loss, and (2) the bandwidth overhead of our scheme is only slightly higher than that of PFC.